Long term survival with stereotactic ablative radiotherapy (SABR) versus thoracoscopic sublobar lung resection in elderly people: national population based study with propensity matched comparative analysis. (8th July 2016) - Paul, Subroto; Lee, Paul C; Mao, Jialin; Isaacs, Abby J; Sedrakyan, Art
Abstract : Objectives To compare cancer specific survival after thoracoscopic sublobar lung resection and stereotactic ablative radiotherapy (SABR) for tumors ≤2 cm in size and thoracoscopic resection (sublobar resection or lobectomy) and SABR for tumors ≤5 cm in size. Design National population based retrospective cohort study with propensity matched comparative analysis. Setting Surveillance, Epidemiology, and End Results (SEER) registry linked with Medicare database in the United States. Participants Patients aged ≥66 with lung cancer undergoing SABR or thoracoscopic lobectomy or sublobar resection from 1 Oct 2007 to 31 June 2012 and followed up to 31 December 2013. Main outcome measures Cancer specific survival after SABR or thoracoscopic surgery for lung cancer. Results 690 (275 (39.9%) SABR and 415 (60.1%) thoracoscopic sublobar lung resection) and 2967 (714 (24.1%) SABR and 2253 (75.9%) thoracoscopic resection) patients were included in primary and secondary analyses. The average age of the entire cohort was 76. Follow-up of the entire cohort ranged from 0 to 6.25 years, with an average of three years. In the primary analysis of patients with tumors sized ≤2 cm, 37 (13.5%) undergoing SABR and 44 (10.6%) undergoing thoracoscopic sublobar resection died from lung cancer, respectively. The cancer specific survival diverged after one year, but in the matched analysis (201 matched patients in each group) there was no significant difference between the groups (SABR v sublobar lung resection mortality: hazard ratio 1.32, 95% confidence interval 0.77 to 2.26; P=0.32). Estimated cancer specific survival at three years after SABR and thoracoscopic sublobar lung resection was 82.6% and 86.4%, respectively. The secondary analysis (643 matched patients in each group) showed that thoracoscopic resection was associated with improved cancer specific survival over SABR in patients with tumors sized ≤5 cm (SABR v resection mortality: hazard ratio 2.10, 1.52 to 2.89; P<0.001). Estimated cancer specific survival at three years was 80.0% and 90.3%, respectively. Conclusions This propensity matched analysis suggests that patients undergoing thoracoscopic surgical resection, particularly for larger tumors, might have improved cancer specific survival compared with patients undergoing SABR. Despite strategies used in study design and propensity matching analysis, there are inherent limitations to this observational analysis related to confounding, similar to most studies in healthcare of non-surgical technologies compared with surgery. As the adoption of SABR for the treatment of early stage operable lung cancer would be a paradigm shift in lung cancer care, it warrants further thorough evaluation before widespread adoption in practice.